2014
DOI: 10.1016/j.egypro.2014.10.155
|View full text |Cite
|
Sign up to set email alerts
|

Pineapple Drying Using a New Solar Hybrid Dryer

Abstract: This paper presents the results of an experimental pineapple (Ananas comosus L.) drying study in a new solar hybrid dryer. The dryer is a direct and integrated type, with a black mate pan which measures 1.675 x 0.61 x 0.055 m (1.02 m 2 ). It uses a copper helical tube that conducts hot water, at 80°C, generating extra heat for the drying process; the tube is located at the bottom of the black pan. A caliber 6, transparent vinyl film is used as a cover and the walls and base of the dryer are isolated by 0.0254 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…Energies 2019, 12, x FOR PEER REVIEW 3 of 18 mixed mode [53] or hybrid [54] dryers, where both direct and indirect solar radiation is in effect or different hot media are used instead of air, respectively.…”
Section: Circular Economy Strategy For Pineapple Processing In Togomentioning
confidence: 99%
“…Energies 2019, 12, x FOR PEER REVIEW 3 of 18 mixed mode [53] or hybrid [54] dryers, where both direct and indirect solar radiation is in effect or different hot media are used instead of air, respectively.…”
Section: Circular Economy Strategy For Pineapple Processing In Togomentioning
confidence: 99%
“…An additional heat source can be incorporated into a solar dryer to reduce the dependency of the drying process on solar radiation; such a solar dryer is commonly referred to as a hybrid solar dryer. The incorporation of an energy source that is not dependent on the weather (e.g., biomass, electricity, or liquefied petroleum gas) allows a continuous process that can be performed during bad weather or at night (Gudiño-Ayala & Calderón-Topete, 2014). Several researchers investigating the application of hybrid solar dryers on various crops, such as mushrooms (Reyes et al, 2014), chamomile (Amer et al, 2018), mint (Eltawil et al, 2018), and maize (Bosomtwe et al, 2019), have observed that the usage of a hybrid solar dryer improves the drying process when compared with a normal solar dryer.…”
Section: Introductionmentioning
confidence: 99%
“…To solve this problem, an additional heat source is equipped to the solar dryer, thereby enabling operation regardless of the weather conditions. These dryers are called hybrid solar dryers due to the implementation of solar energy and conventional energy sources (Gudiño-Ayala & Calderón-Topete, 2014). Various types of hybrid solar dryers have been developed for many agricultural products, such as solar biomass hybrid dryer for maize (Bosomtwe et al, 2019) and gas-fired hybrid solar dryer for onion and ginger (Anum, Ghafoor, & Munir, 2017).…”
mentioning
confidence: 99%